Enriching the experience of patients on a hospice ward with volunteer carers. Issue 2 (1st September 2011) - Carpenter, Jane
Abstract : Introduction: We are working in a difficult global economic climate, increasingly caring for patients with complex needs. As a local charity we need to make best use of our resources, spend donated money in the most responsible manner while continuing to expand patient care services, maintaining the highest quality of patient focused care. Aim: To develop volunteers to undertake clinical activity and enhance the inpatient experience, making better use of all resources. Methods: The ward volunteers were approached with a proposal to expand their role. The staff were informed of the plans and their concerns addressed at an early stage; they were involved throughout the project. The plan followed was: ▶ A consultative approach ▶ Volunteer skills portfolios developed ▶ Ward competencies, supervised practice and classroom based training for volunteers ▶ Initial focus – patient nutrition and oral care ▶ Subsequent introduction of hygiene care. Results: An increasingly confident and flexible volunteer workforce with more involvement in clinical patient care. An efficient use of resources, releasing staff to focus on complex aspects of care, Volunteers are now offering ward administrative support, helping patients with creative activities and are becoming integral to all aspects of ward activity. Discussion and conclusion: Developing volunteers in this way has taken investment of time and staff resources, resulting in an increased richness to the inpatient environment. Volunteers now utilise other skills so that they can participate more fully in the ward domain. Ward nurses now appreciate the volunteer input and rely on their presence; the changes have enhanced our skill-mix and increased our staff: patient ratios.